Impact of headache on postural balance and perception of dizziness in women (Research, Society and Development, 2020)
The purpose of this study is to analyze the occurrence of headache among women complaining of dizziness and to verify the relationship between the presence of headache and the results of posturography and the handicap caused by dizziness. It is an observational, cross-sectional research, quantitative analysis, performed through a database of 216 exams were selected 49 of women complaining of dizziness, between November 2016 and November 2017. The patients were submitted to anamnesis, Foam-Laser Dynamic Posturography (FLP) and the Dizziness Handicap Inventory (DHI) quality of life questionnaire. Comparative inferential analysis was performed using the parametric Student T Test and the non-parametric Mann-Whitney U Test. the sample presented mean age of 57.7 years, all with complaints of dizziness, of which 30 were of long duration, six of short duration and 13 did not know to refer. Twenty-four patients reported headache, 14 of them bilateral. Nineteen women had a diagnosis of vestibular dysfunction. In the posturographic evaluation, the values, on average, were lower than the PFL standard without relation to the presence of headache. However, in relation to quality of life the total sample presented a severe participation restriction with a significant relation for the group with headache. The presence of headache was an aggravation of the participation restriction caused by dizziness, although it did not significantly influence postural balance in the present sample